2004
DOI: 10.1016/j.elecom.2004.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of PbO2 on glassy carbon electrodes: influence of ultrasound frequency

Abstract: The influence of the ultrasonic frequency on the electrocrystallisation of lead dioxide on glassy carbon electrodes was studied in 1 mol dm -3 HNO 3 + 0.1 mol dm -3Pb(NO 3 ) 2 using chronoamperometry and numerical approximations of the current transients obtained. The effects of the ultrasound frequency have been compared with the effects produced by other operational variables such as electrode potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…deposition of Pt on freshly polished Al electrode, for this experiment an ''induction time'' is observed. For nucleation and growth of Pt particles on Al 2 O 3 /Al electrode at À0.6 V, the obtained results from the current-time transients of the Al 2 O 3 /Al electrode in deposition solution and analysis of data according to the literature [38][39][40] showed that the induction time is 1573 s. After applying of an overpotential about À1.0 V for the formation of the first nucleus and then reversing the potential scanning toward anodic scan, the reduction of Pt (IV) ions produce the cathodic currents from À1.0 to 0.0 V, and a symmetric cathodic peak appeared at À0.87 V. As seen in Fig. 1(B) in this case the anodic peak does not appear because of perfect pre-covering of the Al surface by Al 2 O 3 oxide.…”
Section: Surface Modification Of Aluminum Electrodementioning
confidence: 99%
“…deposition of Pt on freshly polished Al electrode, for this experiment an ''induction time'' is observed. For nucleation and growth of Pt particles on Al 2 O 3 /Al electrode at À0.6 V, the obtained results from the current-time transients of the Al 2 O 3 /Al electrode in deposition solution and analysis of data according to the literature [38][39][40] showed that the induction time is 1573 s. After applying of an overpotential about À1.0 V for the formation of the first nucleus and then reversing the potential scanning toward anodic scan, the reduction of Pt (IV) ions produce the cathodic currents from À1.0 to 0.0 V, and a symmetric cathodic peak appeared at À0.87 V. As seen in Fig. 1(B) in this case the anodic peak does not appear because of perfect pre-covering of the Al surface by Al 2 O 3 oxide.…”
Section: Surface Modification Of Aluminum Electrodementioning
confidence: 99%
“…Sonoelectrochemical processes have been deeply studied by the authors in two different application areas: the sonoelectrodeposition of PbO 2 on various substrates [7][8][9] and the sonoelectrochemical removal of organic compounds such as trichloroacetic acid [10] or perchloroethylene [11] in water. The latter constitutes an interesting option for environmental remediation, as complete degradation of C-Cl bonds, which are toxic in nature, is achieved [12].…”
Section: Introductionmentioning
confidence: 99%
“…1 ISE member. compared to the chemically prepared one. The electrodeposition of PbO 2 achieved on various substrates including glassy carbon [9], gold [10], platinum [11], Ebonex [13,14] and lead or lead alloy [12] by means of various electrochemical methods such as cyclic voltammetry [14,15], constant current and constant voltage [15] approaches.…”
Section: Introductionmentioning
confidence: 99%